Do investors over-anticipate? : Evidence from their reactions to gain and loss contingencies - Xu, Tu (2017)
Firms are required to communicate uncertainties about their future earnings and cash flows to investors. In this thesis, I conducted a between-participants experiment to examine how investors anticipate firms’ uncertain future outcomes in response to contingency disclosures. I find that, inconsistent with expected utility theory but consistent with findings from psychology, investors raise a firm’s valuation in response to a gain contingency as if the gain contingency has realized its best possible outcome. At the same time, they lower a firm’s valuation more for a loss contingency than for a realized loss that is essentially the worst possible outcome of the corresponding loss contingency. The effect of anticipation on investors’ valuation judgments is mediated by investors’ uncertainty perceptions. My findings have implications for investors, managers, and regulators.